Estimating households' willingness to pay - Rachel Griffith; Lars Nesheim (Centre for Microdata Methods and Practice (cemmap), 2010)
The recent literature has brought together the characteristics model of utility and classic revealed preference arguments to learn about consumers' willingness to pay. We incorporate market pricing equilibrium conditions into this setting. This allows us to use observed purchase prices and quantities on a large basket of products to learn about individual household's willingness to pay for characteristics, while maintaining a high degree of flexibility and also avoiding the biases that arise from inappropriate aggregation. We illustrate the approach using scanner data on food purchases to estimate bounds on willingness to pay for the organic characteristic. We combine these estimates with information on households' stated preferences and beliefs to show that on average quality is the most important factor affecting bounds on household willingness to pay for organic, with health concerns coming second, and environmental concerns lagging far behind.
Keywords: D12; L11; L81; Q51; C81; 330; Biokost; Hedonischer Preisindex; Konsumentenverhalten; Offenbarte Präferenzen; Willingness to pay; Theorie